2021
DOI: 10.1038/s41598-020-80940-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential organ-specific inflammatory response to progranulin in high-fat diet-fed mice

Abstract: Progranulin (PGRN) has been reported to bind tumor necrosis factor (TNF) receptor and to inhibit TNFα signaling. We evaluated the effect of augmentation of TNFα signaling by PGRN deficiency on the progression of kidney injury. Eight-week-old PGRN knockout (KO) and wild-type (WT) mice were fed a standard diet or high-fat diet (HFD) for 12 weeks. Albuminuria, markers of tubular damage, and renal mRNA levels of inflammatory cytokines were higher in HFD-fed KO (KO-HFD) mice than in HFD-fed WT (WT-HFD) mice. Body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…In particular, high levels of PGRN inhibit insulin signaling and glucose uptake both in vitro and in vivo and may be involved in the development of obesity-associated insulin resistance, while deficiency of PGRN provides protective action in this condition (41). In addition, our previous study demonstrated that PGRN deficiency exacerbated renal inflammation despite improving systemic inflammation in adipose tissue in mice with HFD-induced obesity (42). Therefore, PGRN may have two absonant effects, depending on the disease stage and tissue microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, high levels of PGRN inhibit insulin signaling and glucose uptake both in vitro and in vivo and may be involved in the development of obesity-associated insulin resistance, while deficiency of PGRN provides protective action in this condition (41). In addition, our previous study demonstrated that PGRN deficiency exacerbated renal inflammation despite improving systemic inflammation in adipose tissue in mice with HFD-induced obesity (42). Therefore, PGRN may have two absonant effects, depending on the disease stage and tissue microenvironment.…”
Section: Discussionmentioning
confidence: 94%
“…Excessive high‐fat food can lead to lipid metabolism disorder, activate the inflammation in the body, and cause inflammatory diseases in various organs (Murakoshi et al., 2021 ). This inflammation can cause the increase in inflammatory factors and attract the invasion of inflammatory cells such as lymphocytes and macrophages (Desai et al., 2017 ; Liu et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…mRNAs were isolated from the kidney cortex and gene expression was analyzed using qPCR, as described previously [ 13 ]. For total RNA purification, the RNeasy Mini Kit (Qiagen, Hilden, Germany) was used according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%